The sunset years of Agnes Sharp - Swann, Leonie, 1975- (The Agnes Sharp mysteries, 2023)
"It has been an eventful morning for Agnes Sharp and the other inhabitants of Sunset Hall, a communal home for the old and unruly in the sleepy English countryside. Although they have had their share of issues (misplaced reading glasses, conflicting culinary tastes, mobility issues, and unruly grandsons), nothing prepares them for an unexpected visit from a police officer with some shocking news. The body of one of their neighbors was discovered earlier that morning on the lawn. The members of the house put on long faces when the officer begins asking questions, but they are secretly relieved the body in question is not the one they're currently hiding in the shed (sorry, Lillith). After holding an emergency house meeting, they decide that the answer to their little problem with Lillith may have fallen right into their lap. All they have to do is find out who murdered their neighbor, so they can pin Lillith's death on them, thus killing two (old) birds with one stone (cold killer). With their plan sorted, Agnes and her geriatric gang spring into action. After all, everybody likes a good mystery. Besides, the more suspicion they can cast about, surely the less will land on them. To investigate, they will have to leave their comfort zone and journey into the quaint village of Duck End and all around town as they tangle with sinister bakers, broken stairlifts, inept criminals, local authorities, and their own dark secrets"--